Pengaruh Kecerdasan Emosional Terhadap Akhlak Islamiya - Nugraheni, Fiqi Syarifa (CV. Green Publisher Indonesia, 2025)
Emotions are one of the psychological aspects that have an important role in determining the quality of human behavior in carrying out tasks and social relationships with others in daily life. In learning together and interacting with others, it requires the ability to manage emotions well, controlled emotional conditions will be able to bring harmonious relationships and encouragement in learning activities, but it is better when the management of uncontrolled emotions or unstable emotions will lead to disharmonious relationships and lack of enthusiasm in learning. An unharmonious relationship will have an effect on the quality of the learning process, and social problems between the interacting individuals. Islam advocates being able to manage emotions well, controlled and mature emotional management can make it easier for Muslims to develop or increase their understanding of Islamic values and can improve friendship relations among Muslims and between other religious people. In Islam, humans are required to have guidelines for life in the form of the Quran and As Sunnah. The Quran and As Sunnah provide direction and guidance for humans on all matters of life, whether it is about social society or lessons about other realms of life. Humans face many problems in their lives, whether they are pleasant or unpleasant. Basically, humans tend to choose things that make them happy or feel good. However, humans cannot control what happens. Stress can be caused by problems, conflicts, or obstacles in meeting expectations. Therefore, there are people who are easily discouraged in living their lives, and others who are firm and strong in dealing with problems. People who live by guidelines or principles will be different in dealing with problems with people who don't. The Quran and As Sunnah have provided an example as well as a guideline for humans to live life. The method in this writing is a literature study, namely by explaining and analyzing several psychological theories and studies in Islam on Emotional Intelligence. With the aim of describing the importance of managing emotions in daily life that affect human moral attitudes.